2003
DOI: 10.1242/dev.00854
|View full text |Cite
|
Sign up to set email alerts
|

bullwinkleandsharkregulate dorsal-appendage morphogenesis inDrosophilaoogenesis

Abstract: bullwinkle (bwk) regulates embryonic anteroposterior patterning and, through a novel germline-to-soma signal, morphogenesis of the eggshell dorsal appendages. We screened for dominant modifiers of the bullwinkle mooseantler eggshell phenotype and identified shark, which encodes an SH2-domain, ankyrin-repeat tyrosine kinase. At the onset of dorsal-appendage formation, shark is expressed in a punctate pattern in the squamous stretch cells overlying the nurse cells. Confocal microscopy with cell-type-specific mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…The current published data support the hypothesis that BWK may regulate morphogenesis via a signaling pathway that is neither dependent on GRK/EGFR (Rittenhouse and Berg, 1995) nor on the JNK or DPP signaling pathways, assuming the involvement of another, yet unknown pathway (Tran and Berg, 2003). The results presented here suggest that spoon may participate in this pathway.…”
Section: Figsupporting
confidence: 85%
See 1 more Smart Citation
“…The current published data support the hypothesis that BWK may regulate morphogenesis via a signaling pathway that is neither dependent on GRK/EGFR (Rittenhouse and Berg, 1995) nor on the JNK or DPP signaling pathways, assuming the involvement of another, yet unknown pathway (Tran and Berg, 2003). The results presented here suggest that spoon may participate in this pathway.…”
Section: Figsupporting
confidence: 85%
“…The results presented here suggested that in addition to its roles in the GRK/EGFR and DPP pathways, spoon may be involved in other unrelated pathways including pathways involved in actin polymerization, BC migration, and additional pathways such as the bwk/shark pathway (Tran and Berg, 2003) and cup. …”
Section: Discussionmentioning
confidence: 82%
“…It may occur via Shark, a kinase that has been shown to interact with both Drpr and JNK in Drosophila (Fernandez et al, 2000;Tran and Berg, 2003;Ziegenfuss et al, 2008). Another candidate is Rac1, which can act upstream of JNK and may act downstream of Drpr (Kinchen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, the Gurken ligand concentrated in the anterodorsal corner of the oocyte signals to the main-body FCs associated with this region, which then adopt a dorsal fate (for reviews, see Dobens and Raftery, 2000;Dorman et al, 2004). One of the consequences of this dorsal signaling is the formation of two dorsolateral patches of FCs that migrate anteriorly over the surface of the SCs, where they form two elongated tubes (Tran and Berg, 2003;Dorman et al, 2004). During choriogenesis these tubes participate in the formation of dorsal (respiratory) appendages of the eggshell.…”
Section: Introductionmentioning
confidence: 99%